The effect of exposure to a high-fat diet on microRNA expression in the liver of blunt snout bream (Megalobrama amblycephala). - Dingdong Zhang; Kangle Lu; Zaijie Dong; Guangzhen Jiang; Weina Xu; Wenbin Liu (PLoS ONE)
Blunt snout bream (Megalobrama amblycephala) are susceptible to hepatic steatosis when maintained in modern intensive culture systems. The aim of this study was to investigate the potential roles of microRNAs (miRNAs) in diet-induced hepatic steatosis in this species. MiRNAs, small non-coding RNAs that regulate gene expression at the posttranscriptional level, are involved in diverse biological processes, including lipid metabolism. Deep sequencing of hepatic small RNA libraries from blunt snout bream fed normal-fat and high-fat diets identified 202 (193 known and 9 novel) miRNAs, of which 12 were differentially expressed between the normal-fat and high-fat diet groups. Quantitative stem-loop reverse transcriptase-polymerase chain reaction analyses confirmed the upregulation of miR-30c and miR-30e-3p and the downregulation of miR-145 and miR-15a-5p in high-fat diet-fed fish. Bioinformatics tools were used to predict the targets of these verified miRNAs and to explore potential downstream gene ontology biological process categories and Kyoto Encyclopedia of Genes and Genomes pathways. Six putative lipid metabolism-related target genes (fetuin-B, Cyp7a1, NADH dehydrogenase (ubiquinone) 1 beta subcomplex subunit 2, 3-oxoacid CoA transferase 1b, stearoyl-CoA desaturase, and fatty-acid synthase) were identified as having potential important roles in the development of diet-induced hepatic steatosis in blunt snout bream. The results presented here are a foundation for future studies of miRNA-controlled lipid metabolism regulatory networks in blunt snout bream.